Hierarchical mesoporous bio-polymer/silica composites co-templated by trimethyl chitosan and a surfactant for controlled drug delivery - Rana, Vijay Kumar; Park, Sung Soo; Parambadath, Surendran; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Medchemcomm, 2011)
In this communication, we report the facile synthesis of hierarchical mesoporous bio-polymer/silica composite materials with bimodal mesopores using a dual-template of the cationic N,N,N-trimethyl chitosan (TMCs) and the anionic sodium dodecyl sulfate (SDS) via one-step synthetic strategy. Tetraethoxysilane (TEOS) was used as a silica source. The nitrogen adsorption/desorption measurements and transmission electron microscopy analysis showed the hierarchical structure of the mesoporous bio-polymer/silica composites with bimodal mesopores having an average pore size of 5-7 nm with the visible voids between the silica nanoparticles, which allow the mesoporous bio-polymer/silica composites to encapsulate a large number of guest drug molecules, Ibuprofen (IBU) or 5-fluorouracil (5-FU), due to their high surface area and pore volume. In addition, the mesoporous chitosan-silica composites also had a long term biocompatibility for the target release of the drug molecules to the CEM cells, MCF cells, etc. as well as a pH sensitive controlled release behavior of the drug molecules.

Synthesis and drug-delivery behavior of chitosan-functionalized graphene oxide hybrid nanosheets - Rana, Vijay Kumar; Choi, Myeon-Cheon; Kong, Jin-Yeon; Kim, Gwang Yeon; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Macromolecular Materials and Engineering, 2011)
Chitosan-functionalized graphene oxides (FGOCs) were successfully synthesized. FGOCs were found to significantly improve the solubility of the GO in aqueous acidic media. The presence of organic groups was confirmed by means of XPS and TGA. Restoration of the sp(2) carbon network and exfoliation of graphene sheets were confirmed by Raman spectroscopy, UV-visible spectroscopy and WAXD. The SEM and AFM investigations of the resultant FGOCs showed that most of the graphene sheets were individual and few were layered. Controlled release behavior of Ibuprofen and 5-fluorouracil was then investigated. We found that FGOCs are a promising new material for biological and medical applications.
Keywords: Biocompatibility; Chitosan; drug delivery systems; functionalization of polymers; solution properties